2021
DOI: 10.32749/nucleodoconhecimento.com.br/health/bilateral-tapia
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral tapia syndrome after maxillomandibular advancement surgery

Abstract: Lesions of the hypoglossal and laryngeal nerve, recurrent in its unilateral or bilateral extracranial pathways, cause a motor deficit in the tongue with transient, partial or total loss of speech, which may be associated with mild or severe dysphagia, characterizing Tapia syndrome. This unusual condition is usually related to airway manipulation during anesthetic-surgical surgery, and few cases in the literature are correlated with maxillofacial surgeries, which partly explains the ignorance of this complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We conducted a literature review of studies related to HNP and maxillofacial surgery, and the review revealed several reports of the incidence of HNP following maxillofacial-related surgery ( Table 2 ). Six of the seven studies identified showed that the majority of patients with HNP or Tapia's syndrome have been male, with the age range 22–55 years [ [13] , [14] , [15] , [16] , [17] , [18] ]. Anatomical aspects are more likely to be a factor predisposing to HNP in male patients (in particular, the length of the greater cornu and a larger hyoid volume), and earlier ossification of the connection between the hyoid body and greater cornu was described in prior studies [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We conducted a literature review of studies related to HNP and maxillofacial surgery, and the review revealed several reports of the incidence of HNP following maxillofacial-related surgery ( Table 2 ). Six of the seven studies identified showed that the majority of patients with HNP or Tapia's syndrome have been male, with the age range 22–55 years [ [13] , [14] , [15] , [16] , [17] , [18] ]. Anatomical aspects are more likely to be a factor predisposing to HNP in male patients (in particular, the length of the greater cornu and a larger hyoid volume), and earlier ossification of the connection between the hyoid body and greater cornu was described in prior studies [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The onset of symptoms in HNP patients has been observed on the first postoperative day and has often been recognized ≥5 days postsurgery. Two of the reported patients showed clinical symptoms on the first and second postoperative days, respectively [ [14] , [15] , [16] , 18 ]. Delayed HNP symptoms can develop after a patient's discharge and remain undiagnosed for several reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations